Implementing effective code reviews : how to build and maintain clean code - Carullo, Giuliana (Apress, 2020)
"The ideal code review process differs from organization to organization, but the needs all boil down to the same foundational factors. A software development team cannot properly grow if its code reviews are not consistent, straightforward, and aspire to hit several company goals at once, such as security, performance, longevity, and more. Implementing Effective Code Reviews is the manual your team has been seeking. Author Giuliana Carullo uses her expert background to guide you through the basics of building and maintaining clean code, and she is known for distilling complex concepts into entertaining and easy-to-grasp lessons. Healthy code requires incremental improvements, and knowing how to execute this is essential for conducting effective reviews on your team. While complex and fancy code can be interesting to work with, it will not always achieve business goals or solve urgent problems. Good coding practices are at the heart of a high-performing team, and Carullo instills these core values in a simple, straight-forward way in Implementing Effective Code Reviews. Whether you are a passionate programmer looking to go the extra mile at the office, or an experienced software engineer seeking a guide to how to improve your leadership and code review process, this book covers it all. With each chapter wrapped up in a handy checklist of crucial takeaways, Carullo has created an essential handbook for coders everywhere. There are a lot of myths that dominate the programming landscape, and Implementing Effective Code Reviews grounds the process and gets to the heart of the matter."--Publisher